Analisis Kadar Digoksin Dalam Sediaan Tablet Generik Dari 4 Pabrik Dengan Metode KCKT - Kartika Mutiara Ningtyas (Poltekkes Kemenkes Bandung, 2018)
Digoxin tablets is an inotropic drug that can increase the strength of heart contractions in patients with heart failure. The purpose of these study was to determine the digoxin levels in the generic digoxin tablet preparations from 4 factories and compare the results of the determination with Indonesian Pharmacope 5th. edition requirement. In these study, the method used for determining digoxin tablet wa HPLC, using C18 column (4.6 mm x 150 mm ) as stationary phase, aquadest : acetonitrile (75:25) as mobile phase, 0.5 mL / min flow rate, and UV detector with 220 nm wavelength. The analytical methods were validated based on linearity, LoD and LoQ, accuracy and precision. The linearity test results from 7 variations of concentration (5, 10, 15, 20, 25, 30, and 35 ppm) with correlation coefficient (r) = 0.9973. LoD and LoQ values ​​were 0.0006 mg / L and 0.0021 mg / L, and accruracy is 101.58% and RSD value is 0.924%. From the results of study, obtained the following levels of samples A 97.12%, samples B 89.64%, samples C 92.23% and sample D 102.54%. Based on the results of these study, 3 out of 4 samples were eligible and the last not eligible with Indonesian Pharmacope 5th edition, which contained not less than 90.0% digoxin and not more than 105.0% of the amount stated on the label.